2009
DOI: 10.1002/pd.2428
|View full text |Cite
|
Sign up to set email alerts
|

Determinates of underutilization of amniocentesis among Israeli Arab women

Abstract: Any program aimed at increasing amniocentesis uptake among Muslim women should be directed to both partners and should emphasize the low risk for miscarriage following the test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
0
18
1
Order By: Relevance
“…The rate of amniocentesis among the Arab women aged ≥35 years (who are eligible for the test free of charge) was only 28.5% in 2010 and 18.5% in 2001 (p = 0.7). This is higher than what was reported for this group in 2005-2007 (13.5%) [4]. Consistent with this low percentage, the prenatal detection rate of Down syndrome was only 34.6% in women ≥35 years in 2010-2011 [5].…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…The rate of amniocentesis among the Arab women aged ≥35 years (who are eligible for the test free of charge) was only 28.5% in 2010 and 18.5% in 2001 (p = 0.7). This is higher than what was reported for this group in 2005-2007 (13.5%) [4]. Consistent with this low percentage, the prenatal detection rate of Down syndrome was only 34.6% in women ≥35 years in 2010-2011 [5].…”
Section: Discussioncontrasting
confidence: 49%
“…Shoham-Vardi et al [11] reported that the main reasons for avoiding prenatal diagnosis in the Bedouin population were oppositions to pregnancy termination because of religious reasons and mistrust in the diagnosis of an existing abnormality. Muhsen et al [4] reported that the underutilization of amniocentesis among women aged ≥35 years was significantly associated with age, religiousness, the perception of amniocentesis as a risky procedure, the spouse's opposition to pregnancy termination, and unemployment (outside the home). These latter factors were not included in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Brajenovic et al reported a statistically significant difference in knowledge scores with respect to educational level. In contrast, no difference was observed regarding their attitudes toward amniocentesis [11]. Julian-Reynier et al [12] reported that educational level had no effect on acceptance of invasive diagnostic procedures.…”
Section: Discussionmentioning
confidence: 83%
“…3 In some clinical settings, amniocentesis or CVS for aneuploidy has been offered to all pregnant women of advanced maternal age. [4][5][6] In other circumstances or countries, discussion of invasive testing may be prompted by a high-risk screening result. 7 However, the opportunity to use non-invasive techniques for some conditions is now feasible 8 and these are increasingly available to women in some countries.…”
mentioning
confidence: 99%